The Medical Management of Paediatric Crohn's Disease: an ECCO-ESPGHAN Guideline Update - van Rheenen, Patrick F; Aloi, Marina; Assa, Amit; Bronsky, Jiri; Escher, Johanna C; Fagerberg, Ulrika L; Gasparetto, Marco; Gerasimidis, Konstantinos; Griffiths, Anne; Henderson, Paul; Koletzko, Sibylle; Kolho, Kaija-Leena; et al. (Journal of Crohn's & colitis, 2021)
OBJECTIVE: We aimed to provide an evidence-supported update of the ECCO-ESPGHAN guideline on the medical management of paediatric Crohn's disease [CD]. METHODS: We formed 10 working groups and formulated 17 PICO-structured clinical questions [Patients, Intervention, Comparator, and Outcome]. A systematic literature search from January 1, 1991 to March 19, 2019 was conducted by a medical librarian using MEDLINE, EMBASE, and Cochrane Central databases. A shortlist of 30 provisional statements were further refined during a consensus meeting in Barcelona in October 2019 and subjected to a vote. In total 22 statements reached ≥ 80% agreement and were retained. RESULTS: We established that it was key to identify patients at high risk of a complicated disease course at the earliest opportunity, to reduce bowel damage. Patients with perianal disease, stricturing or penetrating behaviour, or severe growth retardation should be considered for up-front anti-tumour necrosis factor [TNF] agents in combination with an immunomodulator. Therapeutic drug monitoring to guide treatment changes is recommended over empirically escalating anti-TNF dose or switching therapies. Patients with low-risk luminal CD should be induced with exclusive enteral nutrition [EEN], or with corticosteroids when EEN is not an option, and require immunomodulator-based maintenance therapy. Favourable outcomes rely on close monitoring of treatment response, with timely adjustments in therapy when treatment targets are not met. Serial faecal calprotectin measurements or small bowel imaging [ultrasound or magnetic resonance enterography] are more reliable markers of treatment response than clinical scores alone. CONCLUSIONS: We present state-of-the-art guidance on the medical treatment and long-term management of children and adolescents with CD.
Keywords: Crohn’s disease/therapy; algorithms; child; Practice guideline